THE CONTRIBUTION OF THE TEMURIAN QUEENS TO THE PROSPERITY OF CULTURAL LIFE IN THE EXAMPLE OF GAVHARSHODBEGIM - Shakhnoza Shamsiddinova (International Scientific and Current Research Conferences, 2022)
This article discusses the development of science during the Timurid period and the role of the Timurid princesses in the analysis of historical sources and scientific literature. In particular, Gavharshodbegim's active policy in public administration, as well as her contribution to the development of science is highlighted.